Ice training vs dry training - Walters, J. (1999)
Coaches are often faced with the problems of trying to determine the proper mix of dry training and ice training, especially when ice is available throughout the season. Certainly, a skater must spend time on the ice to improve technique and perform the relatively expensive testing procedures of the National Team, yet judgements still have to be made regarding the overall ration of ice and dry training. Author offers some suggestions, which may be useful.